2010
DOI: 10.1111/j.1610-0387.2010.07506.x
|View full text |Cite
|
Sign up to set email alerts
|

10 years quality assurance of the dermatologist's procedure. ABD review board part II: 2003–2009

Abstract: The decreased number of dermatologists' reports submitted could be a result of the review process itself. Other factors may include the optimization of the dermatologist's report with a better reimbursement as well as the recent publication of guidelines and continuous education in occupational dermatology with certification of more than 700 dermatologists. These measures of quality assurance are aimed to further optimize the dermatologist's procedure and to allow for improved and more rapid care for patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In Germany, within the dermatologist's procedure of the German Social Accident Insurance (DGUV), dermatologists are encouraged to patch test POM from workplaces in the case of suspected OSD at the expenses of the statutory employers' liability insurance funds. 17 The present study aims at assessing the quality of performance and documentation of patch testing POM in patients with suspected OSD throughout Germany.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Germany, within the dermatologist's procedure of the German Social Accident Insurance (DGUV), dermatologists are encouraged to patch test POM from workplaces in the case of suspected OSD at the expenses of the statutory employers' liability insurance funds. 17 The present study aims at assessing the quality of performance and documentation of patch testing POM in patients with suspected OSD throughout Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Not only the adequate execution but also the adequate documentation of patch tests with POM is crucial, as this is the only way to understand afterwards what exactly was tested and whether the test result is plausible. In Germany, within the dermatologist's procedure of the German Social Accident Insurance (DGUV), dermatologists are encouraged to patch test POM from workplaces in the case of suspected OSD at the expenses of the statutory employers' liability insurance funds 17 . The present study aims at assessing the quality of performance and documentation of patch testing POM in patients with suspected OSD throughout Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conclude that occupational skin diseases result in a reduced quality of life for patients ( 7 , 8 ), and a number of studies show that intervention provides socio-economic benefits, improving both the state of the patients’ skin disease and their quality of life ( 9 ), as measured by the Dermatological Life Quality Index (DLQI). Investigations have shown that intervention measures given to these patients are cost-effective ( 10 ). Authors generally focused on the effect of intervention on dermatitis and quality of life; in the literature we included, the focus was not on individual professions, except for one article on hairdressers ( 11 ).…”
mentioning
confidence: 99%